Students’ Perception on the Implementation of Video Dubbing Project in Teaching Speaking - Sulastri Manurung; Albert Efendi Pohan (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
This study aimed to investigate the students’ perception of using video dubbing project in teaching speaking for fourth semester students UNRIKA in academic year 2018-2019. A set of questionnaires and open-ended interview were conducted to obtain the data. Data were categorized into three levels namely positive, neutral, and negative. The results revealed almost all students perceived positive perception towards the implementation of video dubbing project in teaching speaking. The result of interview was also in line with result obtained through questionnaires. Students admitted that they performed better speaking skill after the implementation of video dubbing. They also felt being engaged in learning activity and triggered them to be more active. They considered video dubbing was fun, challenging, and can be done anytime and anywhere. In light of the findings, it can be considered as a favorable and effective teaching activity to enhance students’ speaking skill.